The social history of railroads: Security and accidents on the tailroads in the Ottoman Empire (1958-1914) - Karatepe, Şahika. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2017., 2017)
This thesis, inspired by studies on infrastructure written from interdiscipli-nary perspectives with the combination of history, sociology, architecture and anthropology, aims to contribute social and labour history which is recently developing in the Ottoman historiography, focusing on the everyday life around the railroads and its environs, in stations and trains for the first time. Focusing on the railroads and its environs as a space, this thesis analyzes the features, which have prevented the safe circulation of train on the tracks and the problems on the control and protection of railroads, which have seen as the economic growth, bureaucratic control and political integrity by the Otto-man Empire in the nineteenth century. Supreme Council issued Police Regu-lation of Ottoman Railroads on June 11, 1867. This regulation, which would construct order and tranquility around the railroads, will be implemented by Ottoman bureaucracy and railroad companies and try to control the area with legal and military tools. But, in this new built environment aftermath of the construction, Ottomans’ everyday practices like walking on the tracks, accom-modation problems, attacks made to the trains and the rails while the political conjuncture was changing with the rise of nationalism in the Ottoman Em-pire, resistances to camel owners to the railroads, accidents caused by human and technological factors, entrance of animals into the area and weather con-ditions affected to travel made difficult to control the area. Thus, this thesis, focusing on the official documents located in the Ministry of Public Works Railroad Department folders, examines the relations among Ottoman bureau-cracy, railroad authorities where Europeans were directors and Ottomans.
Keywords: Railroads and state -- Turkey.; Investments, Foreign -- Turkey.